Pattern search approach to ferromagnetic material modelling. (10th July 2017) - Cardelli, E.; Faba, A.; Pompei, M.; Quondam Antonio, S.
Abstract: This paper deals with possible optimization‐based techniques for the identification of the parameters of Preisach‐inspired phenomenological model of vector hysteresis in ferromagnetic materials. After a summary of the key features of the phenomenological model mentioned above, the description of the identification technique proposed is given. The identification technique is based on a suitable pattern search algorithm and standard measurements. Results for the FeSi Non‐Oriented Grains steel NOG are presented and discussed.